Dietary Inflammatory Index, Obesity, and the Incidence of Colorectal Cancer: Findings from a Hospital-Based Case-Control Study in Malaysia - Nor Hamizah, Shafiee; Nurul Huda, Razalli; Mohd Razif, Shahril; Khairul Najmi, Muhammad Nawawi; Norfilza, Mohd Mokhtar; Ainaa Almarrdhiyah, Abd Rashid; Lydiatul, Shima Ashari; Hamid Jan, Jan Mohamed; Raja Affendi, Raja Ali * (MDPI, 2023)
Obesity-mediated inflammation represents a key connection between the intake of foods with high inflammatory potential and colorectal cancer (CRC) risk. We aimed to explore the association between energy-adjusted dietary inflammatory index (E-DII) in relation to CRC risk in both obese and non-obese subjects. This study included 99 histopathologically confirmed CRC cases, 73 colonic polyps cases, and 141 healthy controls from tertiary medical centres in both urban and suburban areas in Peninsular Malaysia. The subjects were categorised into body mass index (BMI) < 25 kg/m2 and BMI ≥ 25 kg/m2 groups. E-DII scores were computed based on dietary intake assessed using a validated food frequency questionnaire (FFQ). Logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs), adjusted for potential cofounders. The mean dietary energy intake and mean BMI values of the subjects tended to increase as the E-DII scores increased (p for trend < 0.001). E-DII was significantly related to CRC risk only in obese subjects (OR = 1.45; 95% CI = 1.30-1.77; p < 0.001 for trend). Stratified analyses of risk factors showed significant associations between E-DII and CRC risk by age group (p for interaction = 0.030), smoking status (p for interaction = 0.043), and anthropometric indices for both males and females (p for interaction < 0.001) in the most pro-inflammatory E-DII quartile vs. the lowest E-DII quartile. Overall, pro-inflammatory diets were associated with an increased incidence of CRC in the Malaysian population, particularly in obese subjects.